APPLYING SIMULTANEOUS ROUNDTABLE TO IMPROVE GENRE-BASED PARAGRAPH WRITING ABILITY - I Komang Budiarta (Jurnal Santiaji Pendidikan (JSP), 2017)
To write an ‘attention grabbing’ paragraph, the students should do a lot of practices in writing. However, the fact showed that writing skill was frightening and boring skill to learn as lecturers applied boring and monotonous teaching technique. Thus, the present research was mainly intended to answer the following questions: how effective is simultaneous roundtable in improving the students’ genre-based paragraph writing ability? and how do the students respond the application of simultaneous roundtable in teaching genre-based paragraph writing? The subjects of this research were two classes of the second semester students of English Education Study Program Faculty of Teacher Training and Education Mahasaraswati Denpasar University which consisted of 62 students altogether. The design of the present study was classroom action research which were carried out in three cycles. The progressing results of the pre-test, post-test 1, 2 and 3 confirmed that simultaneous roundtable was effective in improving genre-based paragraph writing ability. In addition, the results of the questionnaire showed that most of the subjects agreed on the application of simultaneous roundtable in teaching genre-based paragraph writing.